PROSES â€œAERASI KONTAKâ€ MENGGUNAKAN MEDIA ARANG KAYU UNTUK MENGURANGI DETERJEN DALAM AIR BAKU - Nusa Idaman Said (Jurnal Teknologi Lingkungan, 2004)
Along with the increase of population and industries in Indonesia especially in DKI Jakarta, the river’s water quality for raw water supply for drinking water treatment is decreasing. And society’s growing concern towards sanitation prompted an increase in the usage of detergents as a cleaning item. In effect, waste excerted by these items contributes to that decrease.This decrease in river’s water quality has increase the expense needed to process drinking water out of it. At this time, PAM (Drinking Water Enterprise) use Active Carbon Powder to remove the detergents from raw water by the adsorption method. The Active Carbon Powder is the main reason behind the increase expense as the powder is quite expensive.To counter the problem, an alternative method is a biological process such as an Aeration Contact using a charcoal as a medium. The process utilizes microbe activities within the river’s water itself. Previous experiments resulted in this : A process with a hydraulic retention time of six hours result in a 90,95 % efficiency rate of detergents removal and a 72,22 % efficiency rate of other organic substance removal.